2014
DOI: 10.15511/tahd.14.03142
|View full text |Cite
|
Sign up to set email alerts
|

Çocukların vücut ağırlığı ve görünümleri ile iştahları hakkındaki ebeveyn değerlendirmelerinin nesnel ölçütlerle ilişkisi?

Abstract: The comparison of parent's perception on weight, appearance and appetite of their children with objective criteria E beveynlerin çoğunun çocuklarının vücut ağırlığı ve görünümleri ya da iştahları ile ilgili endişelerinin olması çok yaygın bir durumdur. Çocukluk çağında iştahsızlık ve yeme problemleri nedeniyle doktora getirilen sağlıklı çocukların oranı %20-35 arasında değişmektedir.[¹] Bu durum hekimler tarafından sıklıkla normal durumun abartılması olarak değerlendirilir.Birçok çalışmada ebeveynlerin çocukla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…Lindsay et al (2010) found that the majority of mothers were of the opinion that having a chubby child meant being a good parent which was due to familial and cultural influence, and that some of the mothers perceived their children as skinny even if they had normal weight (13). When the studies conducted in turkey were reviewed, it was determined that, similar to our study findings, most of the families had wrong perceptions about their overweight or obese children's weight (5,10,21). However, contrary to these studies, Aksoy et al (2016) found that the majority of parents with obese children were aware that their children were obese (7).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Lindsay et al (2010) found that the majority of mothers were of the opinion that having a chubby child meant being a good parent which was due to familial and cultural influence, and that some of the mothers perceived their children as skinny even if they had normal weight (13). When the studies conducted in turkey were reviewed, it was determined that, similar to our study findings, most of the families had wrong perceptions about their overweight or obese children's weight (5,10,21). However, contrary to these studies, Aksoy et al (2016) found that the majority of parents with obese children were aware that their children were obese (7).…”
Section: Discussionsupporting
confidence: 71%
“…As the data collection tool, a questionnaire prepared by the researchers within the framework of the literature was used (1,5,10,11) and the data were collected by face-to-face interviews with the mothers. The first part of the questionnaire investigates the demographic characteristics of the mothers such as age, occupation, working status, height, weight, income status, and gender and age of the overweight or obese child, the second part examines the mothers' perceptions of their child's weight, the third part includes the applications that mothers perform for the weight problem of their child (reducing the number of meals, restricting pastries and sugary foods, etc.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Çocukların büyük çoğunluğuna gelir getirici bir işte çalışmayan anneleri bakıyordu ve annelerin az bir kısmının eğitim düzeyi lise ve üzerindeydi (Tablo 1). (2,(7)(8)(9)(10)(11) . Çocuğun vücut ağırlığı ile ilgili yanlış algılar; annenin çocuğunun beslenmesi konusunda zorlayıcı bir tutum sergilemesine ve bu da ebeveyn-çocuk çatışmasına yol açarak aslında problemi olmayan bir çocukta beslenme sorunu gelişmesine yol açabilir.…”
Section: Bulgularunclassified